Little flock - designing and evaluating a mobile application for Christians in house groups - Wang, Zhenyi (2014)
Mobile devices have been bringing changes and convenience to people both in their social and personal lives. Due to the unique features resulting from their mobility and constrained capacity, designing for mobile interfaces has been gaining an increasing interest and discussion in the field of Human Computer Interaction. This paper presents the design and evaluation process of an app to be used in Christian House Groups, following a user-centred approach. The project began with six exploratory interviews, of which the results were used to inform the first low-fidelity prototype on paper. Five users were then invited to evaluate the prototype and hence a refined design was produced in the form of an Interactive Wireframe. A final Highfidelity Prototype was produced after evaluating with another six end users.